Clinical Implementation of Proton Therapy Using Pencil-Beam Scanning Delivery Combined With Static Apertures - Christian Bäumer; Christian Bäumer; Christian Bäumer; Christian Bäumer; Sandija Plaude; Sandija Plaude; Dalia Ahmad Khalil; Dalia Ahmad Khalil; Dalia Ahmad Khalil; Dirk Geismar; Dirk Geismar; Dirk Geismar; et al. (Frontiers in Oncology, 2021)
Proton therapy makes use of the favorable depth-dose distribution with its characteristic Bragg peak to spare normal tissue distal of the target volume. A steep dose gradient would be desired in lateral dimensions, too. The widespread spot scanning delivery technique is based, however, on pencil-beams with in-air spot full-widths-at-half-maximum of typically 1 cm or more. This hampers the sparing of organs-at-risk if small-scale structures adjacent to the target volume are concerned. The trimming of spot scanning fields with collimating apertures constitutes a simple measure to increase the transversal dose gradient. The current study describes the clinical implementation of brass apertures in conjunction with the pencil-beam scanning delivery mode at a horizontal, clinical treatment head based on commercial hardware and software components. Furthermore, clinical cases, which comprised craniopharyngiomas, re-irradiations and ocular tumors, were evaluated. The dosimetric benefits of 31 treatment plans using apertures were compared to the corresponding plans without aperture. Furthermore, an overview of the radiation protection aspects is given. Regarding the results, robust optimization considering range and setup uncertainties was combined with apertures. The treatment plan optimizations followed a single-field uniform dose or a restricted multi-field optimization approach. Robustness evaluation was expanded to account for possible deviations of the center of the pencil-beam delivery and the mechanical center of the aperture holder. Supplementary apertures improved the conformity index on average by 15.3%. The volume of the dose gradient surrounding the PTV (evaluated between 80 and 20% dose levels) was decreased on average by 17.6%. The mean dose of the hippocampi could be reduced on average by 2.9 GyRBE. In particular cases the apertures facilitated a sparing of an organ-at-risk, e.g. the eye lens or the brainstem. For six craniopharyngioma cases the inclusion of apertures led to a reduction of the mean dose of 1.5 GyRBE (13%) for the brain and 3.1 GyRBE (16%) for the hippocampi.